Extrafollicular adenomatoid odontogenic tumor: a case report - Vichattu, Sankar Vinod; George, Arun; Das, Joy R.; Thomas, Atic; K. Sasi, Athira (International Journal of Research in Medical Sciences, 2023)
Adenomatoid odontogenic tumor (AOT), a benign epithelial odontogenic tumor, constitutes around 2-7% of all odontogenic tumors that are biopsied. This lesion is unique with regard to its clinical, radiographic, and histopathological features making its diagnosis more predictable. This article emphasizes an extrafollicular variant of AOT leading to maxillary anterior jaw swelling along with cortical plate expansion, perforation, and root resorption within a short duration of time pointing towards its aggressive nature.